Community Convergence Framework for Solid Waste Management - Situmeang, Yohanes Parlindungan; Bornalo, Joemyline M.; Calig, Nanie R.; Pahuyo, Therese Samantha V.; Tupaz, Aycel N.; Basister, Michel P. Basister; Mahardika, Ida Bagus Komang; Indiani, Ni Luh Putu; Rematwa, Afelinus; Dewi, I Gusti Ayu Adis Puspita; Putra, I Wayan Widiantara (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The Community Convergence Framework for Solid Waste Management is a sound management plan to address the solid waste problem for the Tangkas Organic Fertilizer Facility in Bali, Indonesia and for private and government institutions worldwide. The framework’s components are based on the principle that solid waste management should be a collective effort between local governments, communities, and organic waste processing centres. The management plan is structured so that there is a convergence between these three components. In this way, communities can strive to create a cleaner and healthier environment for current and future generations. This research will guide understanding of waste management's importance and community convergence's role in achieving sustainable solutions. Contribution to Sustainable Development Goals (SDGs) SDG 3: Good Health and Well-being SDG 4: Quality Education SDG 6: Clean Water and Sanitation SDG 11: Sustainable Cities and Communities SDG 12: Responsible Consumption and Production SDG 13: Climate Action SDG 17: Partnerships for the Goals